Manajemen Pendidikan: Desentralisasi dan Kepemimpinan Kependidikan dalam Meningkatkan Mutu Lembaga Pendidikan - Husniah - Achmad; Sri Hartono (Ideas Publishing, 2021)
The era of globalization in the context of education cannot be avoided, the progress of science and technology accompanied by the increasingly rapid flow of world globalization has had its own impact on the world of education. This research aims to provide knowledge and insight for educational practitioners, especially for policy makers in educational institutions to manage educational institutions by utilizing their resources and competencies. This research uses qualitative methods that are literature studies, using descriptive analysis, with collection techniques data through books, journals and related research. The results show that this globalization process requires the nation's millennial generation to respond to the development of the world of education. The enactment of the decentralization policy has an impact on the management of education in Indonesia, especially in areas that have received authority in managing education, and the enactment of educational autonomy gives the head of an educational institution (school) the flexibility to manage the institution he leads into a quality institution. So it can be concluded that the management of educational units at the elementary and secondary education levels applies school-based management as indicated by independence, partnership, participation, openness and accountability. Era globalisasi dalam konteks pendidikan tidak dapat dihindari kehadirannya. Kemajuan ilmu pengetahuan dan teknologi yang disertai dengan semakin kencangnya arus globalisasi dunia membawa dampak tersendiri bagi dunia pendidikan. Penelitian